Going Native in Robert Kroetsch’s Gone Indian - Edwards, Justin D. (Studies in Canadian Literature, 2001)
While many readings of Robert Kroetsch’s Gone Indian focus on the text’s postmodern structural devices, there is yet no reading that concentrates on Kroetsch’s representation of Jeremy’s "Nativeness." Such a focus allows one to explore the way Gone Indian exposes the falseness surrounding the rhetoric of ethnicity by dismantling binary oppositions and challenging the stable norms upon which processes of ethnic categorization rely. Gone Indian can be read as a post-identity quest narrative through which Kroetsch can resist the fixity of ethnic identities without erasing the politics of identity altogether. It is essential to ask, what is invested in the blurring of ethnic identities? By emphasizing the performative quality of ethnic identities, Kroetsch suggests the impossibility of any individual’s claim to an authentic ethnic identity. This suggestion further complicates colonial rhetoric.